Formation of Future Music Art Teacher`s Methodological Competence in the Process of Pedagogical Practice - Bezemchuk, Larisa; Fomin, Volodymyr (Professional Art Education, 2020)
Object. The article`s aim is to study formation of the methodological competence of a music teacher`s potential in practical work as well as to determine the effective forms and methods of professional training of the bachelor students during their pedagogical practice at schools. Methods. Conventional pedagogical research methods were applied: theoretical analysis of scientific and pedagogical literature, comparative analysis, empirical and modeling methods. Results. In the course of the research, the essence of methodological competence in the context of solving the issues of a potential music teacher’s professional training was theoretically substantiated. It is determined that the content of the curriculum for higher education 014 Secondary Education (Music) focuses the applicant of the first bachelor’s degree on the formation of «polyphonic» methodological and pedagogical thinking. It is proved that this type of thinking is a priority one for mastering the methodological constructions of the updated subjects «musical art» and «art». It is covered the conceptual core for structuring of the main professionally oriented academic disciplines: «Methods of music education» and «Pedagogical practice». The basis of such a structuring is a didactic matrix of art lessons of poly-artistic direction. It is proposed to use the principle of interdisciplinary integration for the development of students’ methodological skills in three dimensions of musical art mastering: improvement-transformation-modeling. Modeling of professional situations in the process of pedagogical practice by means of creation of individual methodological maps of students is carried out. A special place in the methodological and practical work of students was taken by various forms of individual creative tasks on music pedagogy. This significantly affected the level of professional training, and separately – the practical and creative component of the formation of the students’ methodological base. Among the methods that aroused the greatest interest of students during pedagogical practice it should be point out the holding of master classes, music-pedagogical trainings, discussions the issues of pupils’ teaching by art means. A wide range of practical issues was solved due to introduction of interactive teaching forms, like «music aquarium», «art cafe», «brainstorming», «facilitation discussion» as well as imitating music and game technologies. Conclusions. Summarizing the results of the study, it can be pointed out that the practical training of a modern music teacher should be carried out in the plane of integration processes affected the renewal of a music lesson as a lesson of poly-artistic content. It is proposed to consider the formation of methodological competence from the standpoint of the systematic approach to teaching. It is carried out modeling of professional situations based on the principles of interdisciplinary integration. It was found that the most effective form of students’ work during school practice is the creation of individual methodological maps.
Keywords: music art teacher; methodological competence; components of the methodological competence; pedagogical practice